2016
DOI: 10.3390/ijms17121995
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Nanoribbons Induce Autophagic Vacuoles in Neuroblastoma Cell Lines

Abstract: Since graphene nanoparticles are attracting increasing interest in relation to medical applications, it is important to understand their potential effects on humans. In the present study, we prepared graphene oxide (GO) nanoribbons by oxidative unzipping of single-wall carbon nanotubes (SWCNTs) and analyzed their toxicity in two human neuroblastoma cell lines. Neuroblastoma is the most common solid neoplasia in children. The hallmark of these tumors is the high number of different clinical variables, ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
5
35
0
Order By: Relevance
“…81 Consistent with our results, previous studies also reported that GO can enter the cells by interacting with the plasma membrane and probably temporarily disrupting the phospholipid bilayer or causing plasma membrane invagination in HepG2 cells and neuroblastoma cell lines, including SK-N-BE(2) and SH-SY5Y. 30,112 Mari et al 30 further demonstrated that GO nanoribbons at low concentrations and within 72 h of exposure induced autophagy in neuroblastoma cell lines. Evidence from the presence of cytoplasmic vacuoles, especially in treated SK-N-BE(2) cells, and the induction of the lysosomal proteins LC3 and beclin, which are markers of autophagy, also confirmed that the autophagy is mainly due to ROS induced by GO.…”
supporting
confidence: 77%
See 4 more Smart Citations
“…81 Consistent with our results, previous studies also reported that GO can enter the cells by interacting with the plasma membrane and probably temporarily disrupting the phospholipid bilayer or causing plasma membrane invagination in HepG2 cells and neuroblastoma cell lines, including SK-N-BE(2) and SH-SY5Y. 30,112 Mari et al 30 further demonstrated that GO nanoribbons at low concentrations and within 72 h of exposure induced autophagy in neuroblastoma cell lines. Evidence from the presence of cytoplasmic vacuoles, especially in treated SK-N-BE(2) cells, and the induction of the lysosomal proteins LC3 and beclin, which are markers of autophagy, also confirmed that the autophagy is mainly due to ROS induced by GO.…”
supporting
confidence: 77%
“…65,77 For instance, mitochondrial depolarization is associated with mitochondrial dysfunction and the overproduction of ROS. 68,78 Recently, Mari et al 30 reported that GO nanoribbons induced toxicity in human neuroblastoma cancer cell lines such as SK-N-BE(2) and SH-SY5Y. Altogether, the combination of GO and AgNPs in a single platform such as GO-AgNPs could modulate the regulation of mitochondria and increase the generation of ROS.…”
Section: Go-agnps Enhance the Generation Of Ros In Sh-sy5y Cellsmentioning
confidence: 99%
See 3 more Smart Citations